Odpowiedź :
Zad.1
[tex]18\%c=0,18c\\[/tex]
Odp. C
Zad.2
[tex]a)-4a+4+9a-2a=(-4a+9a-2a)+4=3a+4\\b)x-3y-4x+3y-2y=(x-4x)+(-3y+3y-2y)=-3x-2y\\c)2x^2+2y-5x-3y-x^2=(2x^2-x^2)-5x+(2y-3y)=x^2-5x-y[/tex]
Zad.3
[tex]a)7a-\frac{1}{3}x~~dla~~a=9\\7*9-\frac{1}{3}*9=63-3=60\\\\b)3b^2+2b~~dla~~b=-3\\3*(-3)^2+2*(-3)=3*9-6=27-6=21\\\\c)(3x+4y)(6-x)~~dla~~x=2~~i~~y=-3\\(3*2+4*(-3))*(6-2)=(6-12)*4=-6*4=-24[/tex]
Zad.4
[tex]I.~~~~3a-4b\\II.~~~3a-4b+3a-2b=(3a+3a)+(-4b-2b)=6a-6b\\III.~~6a-6b-2a-3b=(6a-2a)+(-6b-3b)=4a-9b[/tex]
Zad.5
[tex]I.~~~~15a-10\\II.~~~(15a-10)*2=30a-20\\III.~~(30a-20):5=6a-4[/tex]
Zad.6
[tex]a)(6x-3)-(4x+5)=6x-3-4x-5=(6x-4x)+(-3-5)=2x-8\\b)-3x-(5-x)+3=-3x-5+x+3=(-3x+x)+(-5+3)=-2x-2\\c)(4a-6)+(4a+6)=4a-6+4a+6=(4a+4a)+(-6+6)=8a+0=8a[/tex]
Zad.7
[tex]a)a(6+a^2)-5(2a-a^2)+2a(a^2-1)=6a+a^3-10a+5a^2+2a^3-2a=\\=(a^3+2a^3)+5a^2+(6a-10a-2a)=3a^3+5a^2-6a\\\\b)x^2(yx-y)-y(xy^2-x^2)=x^3y-x^2y-xy^3+x^2y=\\=x^3y+(-x^2y+x^2y)-xy^3=x^3y-xy^3\\\\c)-\frac{2}{3}a(-3b^2-6ab)=-2ab^2+4a^2b=4a^2b-2ab^2[/tex]
Odpowiedź:
Szczegółowe wyjaśnienie:
Zad. 1
C
Zad. 2
a) - 4a + 4 + 9a - 2a = 3a + 4
b) x - 3y - 4x + 3y - 2y = -3x - 2y
c) 2x² + 2y - 5x -3y - x² = x²- 5x - y
Zad. 3
a) 7a - [tex]\frac{1}{3}a[/tex] dla a = 9
7* 9 - [tex]\frac{1}{3}[/tex] * 9 = 63 - 3 = 60
b) 3b² + 2b dla b = - 3
3* (-3)² + 2 * (-3) = 3 * 9 - 6 = 27 - 6 = 21
c) (3x + 4y)(6 - x) dla x = 2 i y = -3
(3 * 2 + 4* (-3)) * (6 - 2) = (6 -12) * 4 = - 6 * 4 = -24
Zad. 4
3a - 4b + 3a - 2b = 6a - 6b
6a - 6b - 2a - 3b = 4a - 9b
Zad. 5
(15a - 10) * 2 = 30a - 20
(30a - 20) : 5 = 6a - 4
Zad. 6
(6x - 3) - (4x + 5) = 6x -3 - 4x - 5 = 2x - 8
- 3x - (5 - x) + 3 = - 3x - 5 + x + 3 = -2x - 2
Zad. 7
a) a(6 + a²) - 5(2a - a²) + 2a(a² - 1) = 6a + a³ - 10a + 5a² + 2a³ - 2a = 3a³ - 5a²- 6a
b) x²(yx - y) - y(xy² - x²) = x³y - x²y - xy³ + x²y = x³y - xy³
c) [tex]-\frac{2}{3}a[/tex] (-3b² - 6ab) =2ab² + 4a²b